Early neurological deterioration with severe headache as the initial manifestation: A case report - Meichun Tao, MD; Yaping Yang, PhD; Hao Cheng, MD; Mei Dong, PhD (Radiology Case Reports)
Severe headache as the initial clinical manifestation of early neurological deterioration (END) is uncommon. The emergence of severe headache should be promptly recognized as a potential indicator of large vessel stenosis. Here, we describe a male patient who initially presented with severe headache accompanied by transient left limb weakness, which subsequently progressed to persistent weakness. Imaging studies revealed severe stenosis at the origin of the right internal carotid artery, along with the presence of asymmetrically prominent cortical veins (APCV). Despite the administration of pregabalin orally and tramadol intramuscularly, his headache persisted. However, significant alleviation of his headache symptoms was observed following the improvement of cerebral perfusion.Re-examination revealed the resolution of cortical vein dilation. This case underscores the importance of recognizing severe headache and APCV as potential indicators of large vessel stenosis and early neurological deterioration (END). Improving cerebral perfusion may serve as an effective means of alleviating headache symptoms in such cases.